The association between adverse childhood experiences and depression trajectories in the Add Health study. (March 2023) - Desch, Jill; Mansuri, Fahad; Tran, Dieu; Schwartz, Skai W.; Bakour, Chighaf
Abstract: Background: Adverse childhood experiences (ACEs) are potentially traumatic experiences that occur before age 18. ACEs are linked to depression in adulthood, but little is known about the association between ACEs and depression trajectories across the lifespan. Objective: To examine the association between specific types of ACEs, cumulative ACE scores, and depression trajectories from adolescence to adulthood. Participants and setting: Waves 1–4 of the National Longitudinal Study of Adolescent to Adult Health (N = 12, 888), spanning ages 12 years to 43 years. Methods: We constructed trajectories of depression scores using a modified 9-item Center for Epidemiologic Studies Depression Scale (CES-D-9). We used weighted logistic regression to calculate odds ratios and confidence intervals for each ACE and ACE score and depression trajectories after adjusting for confounders. Results: We found 75.3 % experienced at least one ACE and 14.7 % experienced 4+ ACEs. We identified three CES-D-9 trajectories: consistently low (Group 1), decreasing (Group 2), and increasing (Group 3) depression scores. All types of abuse, neglect, and community violence were significantly associated with trajectory Groups 2 and 3 vs 1 (p < .05). Foster home placement, poverty, and parental incarceration were associated with Group 2 vs 1. ACE scores showed a dose-response association with Group 3 vs 1 [aORs for 1ACE = 1.43 (0.93–2.20); 2-3ACEs = 1.97 (1.30–3.00); 4+ACEs = 3.08 (1.86–5.09)], and Group 2 vs 1 [aORs for 1ACE = 1.26 (0.87–1.83); 2-3ACEs = 1.93 (1.36–2.74); 4+ACES = 2.70 (1.90–3.84)]. Conclusions: ACEs can have a lasting impact on depression through adulthood, highlighting the need to mitigate their impact to prevent depression-associated morbidity and mortality.